How do banks respond to shocks? A dynamic model of deposit-taking institutions - Dia, Enzo (Journal of Banking & Finance, 2013)
This paper proposes a dynamic model of the optimal choices of a bank that benefits from market power and takes into account the impact of the deposit generation process. Interbank lending/borrowing emerges as a buffer that assists the bank in smoothing intertemporal adjustments in interdependent loan and deposit choices. The bank smooths the impact of interest-rates shocks on its customers to minimize the adjustments over time of the stocks of deposits and loans. It does not, however, provide insurance against negative shocks of real origin that increase its expected default costs. The predictions of the model help to shed light on the available empirical evidence and to analyze some recent developments of the banking industry.